2008
DOI: 10.1051/0004-6361:200810700
|View full text |Cite
|
Sign up to set email alerts
|

Long-term optical monitoring of η Carinae

Abstract: Context. The periodicity of 5.5 years for some observational events occurring in η Carinae manifests itself across a large wavelength range and has been associated with its binary nature. These events are supposed to occur when the binary components are close to periastron. To detect the previous periastron passage of η Car in 2003, we started an intensive, ground-based, optical, photometric observing campaign. Aims. We continued observing the object to monitor its photometric behavior and variability across t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 17 publications
6
71
0
Order By: Relevance
“…(Unfortunately the minimum near 1998.0 is almost unknown.) Fernández-Lajús et al (2010) observed a similar but much less dramatic difference between events at visual wavelengths. In 2008-2009 they observed decreases of 0.15 to 0.25 mag in the UBVRI bands, only 0.02-0.03 mag deeper than during the 2003.5 event.…”
Section: Light Curve Of the Star 2008-2011mentioning
confidence: 73%
See 1 more Smart Citation
“…(Unfortunately the minimum near 1998.0 is almost unknown.) Fernández-Lajús et al (2010) observed a similar but much less dramatic difference between events at visual wavelengths. In 2008-2009 they observed decreases of 0.15 to 0.25 mag in the UBVRI bands, only 0.02-0.03 mag deeper than during the 2003.5 event.…”
Section: Light Curve Of the Star 2008-2011mentioning
confidence: 73%
“…Occasionally its high-excitation He I, [Ne III], [Fe III] emission lines disappear for a few weeks or months (Gaviola 1953;Zanella et al 1984) while other changes also occur, specifically in the X-ray (e.g., Corcoran et al 1997;Ishibashi et al 1999b,a) and infrared flux (e.g., Whitelock et al 1994;Feast et al 2001). These "spectroscopic events" recur with a period close to 2023 days (Damineli 1996;Whitelock et al 1994;Damineli et al 1999Damineli et al , 2000Whitelock et al 2004;Martin et al 2006a;Damineli et al 2008b;Fernández-Lajús et al 2010). They have been attributed to (1) eclipses of a hot secondary star by the primary wind (Damineli et al 1997;Ishibashi et al 1999b;Stevens & Pittard 1999;Pittard & Corcoran 2002); (2) disturbances in the primary wind triggered by a companion star near periastron (Davidson 1997(Davidson , 1999Smith et al 2003;Martin et al 2006a); (3) a thermal/rotational recovery cycle (Zanella et al 1984;Davidson et al 2000;Smith et al 2003;Davidson 2005); or (4) a breakup/collapse of the wind-wind collision structure due to known shock instabilities (Davidson 2002;Soker 2003;Martin et al 2006a;Soker & Behar 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In the optical band, the brightness of η Car increased by several magnitudes during the last ∼30 years (see Fernández-Lajús et al 2009;Gomez et al 2010;Smith & Frew 2011). This increasing optical brightness suggests that the inner envelope, that enshrouds the central star, is currently opening up (Martin et al 2006), and a larger fraction of the stellar optical and UV radiation, that was previously absorbed within the nebula and thus heated the dust, is now able to leave the system.…”
Section: The Far-infrared Spectral Energy Distribution Of η Carinaementioning
confidence: 99%
“…The secondary star has wind parameters indicative of either a WR or extreme O star, with the strongest constraints coming from the X-ray analysis (Pittard & Corcoran 2002;Parkin et al 2009), which points toṀ 2 ≈ 10 −5 M ⊙ yr −1 and v ∞,2 ∼ 3000 km s −1 . η Car has a high eccentricity (∼ 0.9) and an orbital period of 5.54 yr, and many observational phenomena are modulated on this time-scale, such as the X-ray emission (Corcoran 2005, Corcoran et al 2010, multi-wavelength photometry (Fernández-Lajús et al 2003, 2010Whitelock et al 2004), He I narrow emission (Damineli et al 1997), the Hα and other wind line profile morphologies (Richardson et al 2010(Richardson et al , 2015, He II emission from near the colliding winds (Steiner & Damineli 2004;Teodoro et al 2012Teodoro et al , 2016Mehner et al 2015;Davidson et al 2015), and spatiallyextended forbidden line emission (Gull et al 2009(Gull et al , 2011Teodoro et al 2013). The 2003 periastron passage was well-documented thanks to a large Treasury program with the Hubble Space Telescope (HST) and Space Telescope Imaging Spectrograph (STIS) 1 .…”
Section: Introductionmentioning
confidence: 99%